2020
DOI: 10.1111/jphd.12414
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of payer readiness for value‐based care in a fee‐for‐service environment: Measuring provider performance on sealant delivery

Abstract: Objectives: Previously published sealant measures are not useful when applied to Medicaid claims data in states where dental services are carved out of managed care. A novel sealant measure was developed to assess the degree to which dental providers seal eligible teeth during preventive dental visits (PDVs) in an effort to ascertain if such a measure can be used to valuate provider performance, as condition of potential value-based care model implementation. Methods: A single-county feasibility study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The first article describes a Medicaid-based feasibility study of a revised methodology where the measure numerator eliminated teeth previously restored, sealed, or missing, and the denominator was a sealant applied by the same dentists within 9 months of an initial preventive visit. 306 The previously used method did not eliminate unsealable teeth from the numerator. Singlecounty results showed that overall, 11% of all eligible teeth were sealed, and only 9% of dentists applied sealants within the 9-month period to 40% of the eligible teeth.…”
Section: Sealantsmentioning
confidence: 99%
“…The first article describes a Medicaid-based feasibility study of a revised methodology where the measure numerator eliminated teeth previously restored, sealed, or missing, and the denominator was a sealant applied by the same dentists within 9 months of an initial preventive visit. 306 The previously used method did not eliminate unsealable teeth from the numerator. Singlecounty results showed that overall, 11% of all eligible teeth were sealed, and only 9% of dentists applied sealants within the 9-month period to 40% of the eligible teeth.…”
Section: Sealantsmentioning
confidence: 99%
“…45,46 Equitable health care can only occur in an integrated system of value-based care that supports transformations in prevention, treatment, payment models, and data and analytics to deliver patient-centered care and improve population outcomes. 47,48 Public and private insurance programs can be restructured to bundle payments, incentivize prevention and health promotion, and create flexible payment options for health services delivered outside of the clinic via telehealth and home-based care. Payment transformation that occurs through alternative models that incentivize prevention and optimal health lends itself to improved health systems outcomes, especially if the health system works to focus not on disease interventions but on the upstream, localized, and systemic causes of disease.…”
mentioning
confidence: 99%